2017
DOI: 10.1039/c7ee01747b
|View full text |Cite
|
Sign up to set email alerts
|

A prototype reactor for highly selective solar-driven CO2reduction to synthesis gas using nanosized earth-abundant catalysts and silicon photovoltaics

Abstract: The conversion of carbon dioxide (CO2) into value-added chemicals and fuels, preferably using renewable energy and earth-abundant materials, is considered a key priority for future energy research. In this work, a bias-free reactor device for the solar-driven conversion of CO2 to synthesis gas (syngas) has been developed. The integrated fluidic device consists of a cathode made of copper foam coated with low-cost nanosized zinc flakes as catalyst to perform the CO2 reduction reaction (CO2RR) to syngas, an adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 72 publications
3
93
1
Order By: Relevance
“…Previous reports have focused on monometallic molecular and heterogeneous catalytic systems, which have been used for simultaneous production of CO and H 2 . However, single catalytic sites offer limited possibilities for selective tuning of the catalyst.…”
Section: Introductioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Previous reports have focused on monometallic molecular and heterogeneous catalytic systems, which have been used for simultaneous production of CO and H 2 . However, single catalytic sites offer limited possibilities for selective tuning of the catalyst.…”
Section: Introductioncontrasting
confidence: 96%
“…Previous reports have focusedo nm onometallic molecular [4][5][6] and heterogeneousc atalytic systems, [7][8][9][10][11][12][13][14][15] which have been used fors imultaneous production of CO and H 2 .H owever,s ingle catalytic sites offer limited possibilities for selective tuning of the catalyst. Introducing as econd metal site offers an extra degree of freedom in catalystd esign ando ffers the best route to address the above criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have revealed the high‐activity of noble‐metal electrodes (e.g., gold and silver) for CO 2 ‐to‐CO reduction, but the high cost limits the industrial applications. Zinc (Zn) is an earth‐abundant metal and recent studies have demonstrated the capacity of Zn as an efficient electrocatalyst for CO 2 reduction to primarily CO . Won et al.…”
Section: Figurementioning
confidence: 99%
“…[10] Researchers have revealed the high-activity of noblemetal electrodes (e.g.,g old and silver) for CO 2 -to-CO reduction, [11][12][13] but the high cost limits the industrial applications. Zinc (Zn) is an earth-abundantm etal and recent studies have demonstrated the capacity of Zn as an efficient electrocatalyst for CO 2 reduction to primarily CO. [14][15][16][17][18][19] Wone tal. have shown exciting results on ah ierarchical hexagonal Zn catalyst with the maximum selectivityo fa bout9 5% for CO, [14] indicating the decisive role of morphology of different Zn catalysts.…”
mentioning
confidence: 99%
“…The 3 D structure of the applied Ni foam offered a higher active surface area compared with the flat foil, which should be conducive to better HER catalysis of the photocathode. This has been shown elsewhere, and was confirmed herein by the j–V measurement presented in Figure S8 (Supporting Information), proving a shift of the onset potential for the cathodic current density in the anodic direction as well as the steeper slope in the j – V characteristics of the Ni foam compared with a Ni foil electrode. These results were reflected in the linear sweep curves shown in Figure , as the fill factor of the photocathode (filtered) increased significantly, indicating enhanced kinetics of the HER.…”
Section: Resultsmentioning
confidence: 97%